Geometrical comparison of inline and staggered stack wire mesh absorbers for solar volumetric receivers - Daniel Sanchez-Señoran; Miguel A. Reyes-Belmonte; Michael P. Kinzel; Marina Casanova; Antonio L. Avila-Marin (Case Studies in Thermal Engineering)
Open volumetric receivers using air as the heat transfer fluid can operate at higher temperatures and thermal efficiencies than the current state of the art in central receiver systems. Optimising their design requires detailed understanding of two critical operational attributes: the heat transfer coefficient (HTC) and the pressure drop. This work examines these attributes in two dense wire mesh absorber arrangements, inline (IL) and staggered (ST), with single-mesh porosities of 80 % and wire diameters of 0.7, 0.4 and 0.1 mm. A 2D porous model or homogeneous equivalent model (HEM) with local thermal non-equilibrium (LTNE) is developed, using a flux density of 600 kW/m2 and an air inlet velocity of 1 m/s. The model is experimentally validated and subsequently used to evaluate the generalised correlations (GCs) obtained for the thermo-fluid-dynamic attributes with those derived from the individual correlations (ICs). In addition, the model assesses the impact of the different wire diameters and arrangements on thermal and fluid flow performance. The findings reveal that the ST arrangement generally outperforms the IL arrangement in thermal efficiency, except for the 0.1 mm wire diameter. Conversely, the IL arrangement demonstrates superior hydrodynamic performance. Finally, the results are corroborated with existing literature, which further validates the reliability of the numerical model and its conclusions.